2017
DOI: 10.1186/s12887-017-0969-7
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social risk in medical decision-making for physical child abuse: a mixed-methods study

Abstract: BackgroundThe medical literature reports differential decision-making for children with suspected physical abuse based on race and socioeconomic status. Differential evaluation may be related to differences of risk indicators in these populations or differences in physicians’ perceptions of abuse risk. Our objective was to understand the contribution of the child’s social ecology to child abuse pediatricians’ perception of abuse risk and to test whether risk perception influences diagnostic decision-making.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 21 publications
1
21
0
2
Order By: Relevance
“…Since the data show that these parents are less likely to accept HPV vaccine for their teen(s), it may be beneficial to develop promotional messages that resonate with parents with higher levels of education, which may also include parents with higher levels of health literacy. Similar to another analysis, 33 our study also suggests that there may be room to customize interventions by MSA status. For example, in suburban areas, we might consider ways we could reach older mothers, especially those of higher socioeconomic status.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Since the data show that these parents are less likely to accept HPV vaccine for their teen(s), it may be beneficial to develop promotional messages that resonate with parents with higher levels of education, which may also include parents with higher levels of health literacy. Similar to another analysis, 33 our study also suggests that there may be room to customize interventions by MSA status. For example, in suburban areas, we might consider ways we could reach older mothers, especially those of higher socioeconomic status.…”
Section: Discussionsupporting
confidence: 86%
“…20 Results from an additional study found that non-Hispanic white parents of higher socioeconomic status were less likely to accept HPV vaccine for their children. 33 Another analysis identified not having a well-child visit and lack of provider recommendation as factors associated with noninitiation. 30 Teens in mostly rural areas were less likely to initiate HPV vaccination compared to those in mostly urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents who did not receive a provider recommendation were 2 times more likely to report that they did not intend to vaccinate their child in a national survey. 67 Further, health providers have been found to provide recommendations that were not strong or consistent to their patients, and were more likely to be made to females and older adolescents. 68 In order to understand vaccination rates and its effect on HPV prevalence in the United States, it is important to understand the history of vaccination policy and the ensuing barriers.…”
Section: Hpv Vaccination Disparitiesmentioning
confidence: 99%
“…NIS showed that low HPV vaccine uptake (16%) was due to systemic barriers, such as lack of access to clinics during hours of operation. 58 More frequently reported barriers included vaccine misinformation, worry about safety, and lack of knowledge about the vaccine.…”
Section: Future Efforts To Improve Hpv Vaccine Uptakementioning
confidence: 99%